A Review of Research Approaches to Private Intergenerational Transfers - ГладниковаЕкатерина Владимировна (Journal of Economic Sociology, 2010)
The paper presents a review of methodological approaches and empirical research on intergenerational transfers. Economic, sociological and demographic perspectives are considered. The focus is made on the overseas literature supplemented with some results of relevant research on Russia.